Callus induction from tuber of lesser yam (Dioscorea esculenta) on MS media supplemented by 2, 4-D and kinetin. Issue 5 (June 2021) - Habibah, N A; Safitri, S; Pratiwi, Y R; Wijawati, N; Musafa, F; Puspitasari, A D S; Yuniastuti, A
Abstract: Lesser yam contains active pharmaceutical compounds. Secondary metabolic production of lesser yam plants takes time because of the long harvest period. Callus induction can be used to acquire active compounds in relatively short periods. This study aimed to determine the optimum concentration of 2, 4-D and kinetin combination in inducing lesser yam callus in light and dark conditions. The research design used was a two-factor randomized block design, namely the combination of PGR (2, 4-D 1 ppm + kinetin 1 ppm, 2, 4-D 0.5 ppm + kinetin 1 ppm, 2, 4-D 1 ppm + kinetin 0.5 ppm, 2, 4-D 0.5 ppm + kinetin 0.5 ppm) and lightness conditions (light and dark). The observed parameters included callus appearance time, percentage of callus formation, and callus color and texture. The results showed that the combination of 0.5 ppm 2, 4-D + 0.5 ppm kinetin in light conditions indicated the fastest callus time. Meanwhile, the percentage of explants with the highest callus was shown in all treatments in dark conditions by 100%. The calluses produced in light conditions were generally green with a friable texture, calluses in dark conditions were generally white and had friable texture.